Wskaźniki niefinansowe struktury wewnętrznej monitora wartości niematerialnych - Góralski, Bartosz (Non-Financial Indicators of Internal Structure in Intangible Assets Monitor, 2005)
Intangible assets are influencing managers to change the way of doing business. The processes inside corporations determine attitude towards employees, product development, service sales and communication with customers. These fundamental changes are affecting strategies, reputation, short and long term decisions. The drivers of the value of companies are leaning toward intangible assets and force managers to develop new methods of their measurement and presentation. In this article are shown the non-financial indicators of the Internal Structure, which consists of a wide range of patents, concepts, models, and computer and administrative systems.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 186-191